Clinical experience of esophageal perforation occurring with endoscopic submucosal dissection. Issue 7 (1st October 2014) - Sato, H.; Inoue, H.; Ikeda, H.; Grace R. Santi, E.; Yoshida, A.; Onimaru, M.; Kudo, S.
Summary: Esophageal perforation occurring during or after endoscopic mucosal resection (EMR ) or endoscopic submucosal dissection (ESD ) is a rare, but serious complication. However, reports of its characteristics, including endoscopic imaging and management, have not been fully detailed. To analyze and report the clinical presentation and management of esophageal perforations occurred during or after EMR /ESD . Four hundred seventy-two esophageal neoplasms in 368 patients were treated (171 EMR ; ESD 306) at N orthern Y okohama H ospital from 2003 to 2012. Esophageal perforation occurred in a total of seven (1.9%) patients, all of whom were male and had undergone ESD . The etiology of perforation was: three (42.9%) intraoperative; three (42.9%) balloon dilatation for stricture prevention; one (14.2%) due to food bolus impaction. All cases were managed non-operatively based on the comprehensive assessment of clinical severity, extent of the injury, and the time interval from perforation to treatment onset. Conservative management included (i) bed rest and continuous monitoring to determine the need for operative intervention; (ii) fasting and intravenous fluid infusion/ tube feeding; and (iii) intravenous antibiotics. All defects closed spontaneously, save one case where closure was achieved by endoscopic clipping. Surgery was not required. Conservative management for esophageal perforation during advanced endoscopic resection is may be possible when there is no delay in diagnosis or treatment. Decision-making should be governed purely by multidisciplinary discussion.